Short peptide pharmacophores developed from protein phosphatase-1 disrupting peptides (PDPs). (1st July 2022) - Fontanillo, Miriam; Trebacz, Malgorzata; Reinkemeier, Christopher D.; Avilés Huerta, Daniela; Uhrig, Ulrike; Sehr, Peter; Köhn, Maja
Graphical abstract: Highlights: High throughput and structure-based virtual screening assays for PP1 de-inhibition. Optimization of a 23mer PP1-disrupting peptide to a pentapeptide with sub-micromolar activity. Detailed structure–activity relationship study of peptides bound to the RVxF-binding site in PP1. Abstract: PP1 is a major phosphoserine/threonine-specific phosphatase that is involved in diseases such as heart insufficiency and diabetes. PP1-disrupting peptides (PDPs) are selective modulators of PP1 activity that release its catalytic subunit, which then dephosphorylates nearby substrates. Recently, PDPs enabled the creation of phosphatase-recruiting chimeras, which are bifunctional molecules that guide PP1 to a kinase to dephosphorylate and inactivate it. However, PDPs are 23mer peptides, which is not optimal for their use in therapy due to potential stability and immunogenicity issues. Therefore, we present here the sequence optimization of the 23mer PDP to a 5mer peptide, involving several attempts considering structure-based virtual screening, high throughput screening and peptide sequence optimization. We provide here a strong pharmacophore as lead structure to enable PP1 targeting in therapy or its use in phosphatase-recruiting chimeras in the future.